VD_FINDINFO Jug / 2013 / 140 vom 5. Februar 2013 - VD Tribunal cantonal (2013)
CONDUITE EN ÉTAT D'IVRESSE, CIRCULATION ROUTIÈREDROIT DE LA CIRCULATION ROUTIÈRE | 34 CP, 42 al. 1 CP, 42 al. 4 CP, 42 CP, 44 al. 1 CP, 44 CP, 47 CP, 49 CP, 90 ch. 1 LCR, 90 LCR, 91 LCR